Guinayangan CSV experience guides Philippine DA's development of AMIA villages, the Philippine adaptation of CSV approach - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Testing CSV approach in the Philippines, through ICRAF-F2-SEA-P55 project, gained recognition of IIRR by DA as a partner in implementing its AMIA program. DA, through the DA-BAR, invested USD100,000 to further develop Guinayangan CSV as a CSA learning site; and another USD100,000 for IIRR's Ivisan, Capiz project site for same purpose. These sites were used to train regional AMIA teams, particularly in facilitating community-based CSA work and establishing AMIA villages, the country's adaptation of CSV, in 17 regions.